Father Support, Postpartum Depression, and Breastfeeding Weaning Time: A Structural Equational Model - Iskandar, Imelda; Syam, Azniah (Nurse Media Journal of Nursing, 2024)
Background:  Fathers are crucial to family well-being and beyond during pregnancy and childbirth. However, research on the long-term effects of father involvement during prenatal and its postpartum outcome, particularly in Indonesia, is limited.Purpose: This study aimed to measure the direct and indirect effects of father support throughout pregnancy on postpartum depression and breastfeeding weaning time, by considering potential mediating pathways and controlling for relevant sociodemographic variables.Methods: Prospective observational techniques were employed from January to July 2021, involving 648 consecutively selected mothers attending antenatal care in seven health clinics in Makassar. Data collection included sociodemographic factors, father support, and breastfeeding weaning time. Father support was assessed using the Father Support During Pregnancy questionnaire, administered three times at a 72-hour interval. Postpartum depression was measured using the Edinburgh Postnatal Depression Scale while breastfeeding weaning time was quantified in weeks. The analysis included Spearman's correlation and SEM using SPSS and SPSS Amos.Result: The study identified negative correlations between maternal breastfeeding weaning time and postpartum depression (r=-0.183, p<0.01) and positive correlations with father support (r=0.148, p<0.01), parity (r=-0.269, p<0.01), and marital age (r=0.187, p<0.01). The standardized model showed a marginal rise in the overall influence of father support, parity, and marital age on breastfeeding weaning time (0.256, 0.016, and 0.123, respectively). Father support emerged as the primary contributor to postpartum depression, inversely impacting breastfeeding duration. Higher father support correlated with lower maternal depression scores and longer.Conclusion: This study highlights the role of father support in reducing impact of postpartum depression on breastfeeding duration. Future research should incorporate objective measures of father support and comprehensive assessments of confounding variables. Intervention studies are needed to evaluate promoting father involvement in prenatal, delivery, and postpartum care. Nurses can contribute by participating in interdisciplinary research and advocating for comprehensive assessment approaches.